Case Report: Reconstruction of a Large Maxillary Defect With an Engineered, Vascularized, Prefabricated Bone Graft - Ismail, Tarek; Haumer, Alexander; Lunger, Alexander; Osinga, Rik; Kaempfen, Alexandre; Saxer, Franziska; Wixmerten, Anke; Miot, Sylvie; Thieringer, Florian; Beinemann, Joerg; Kunz, Christoph; Jaquiéry, Claude; et al. (Frontiers in Oncology, 2021)
The reconstruction of complex midface defects is a challenging clinical scenario considering the high anatomical, functional and aesthetic requirements. In this study, we proposed a surgical treatment to achieve improved oral rehabilitation and anatomical and functional reconstruction of a complex defect of the maxilla with a vascularized, engineered composite graft. The patient was a 39-year-old female, postoperative after left hemimaxillectomy for ameloblastic carcinoma in 2010 and tumor-free at 5-year oncological follow-up. The left hemimaxillary defect was restored in a two-step approach. First, a composite graft was ectopically engineered using autologous stromal vascular fraction (SVF) cells seeded on an allogenic devitalized bone matrix. The resulting construct was further loaded with bone morphogenetic protein-2 (BMP-2), wrapped within the latissimus dorsi muscle and pedicled with an arteriovenous (AV)-bundle. Subsequently, the prefabricated graft was orthotopically transferred into the defect site and revascularized through microvascular surgical techniques. The prefabricated graft contained vascularized bone tissue embedded within muscular tissue. Despite unexpected resorption, its orthotopic transfer enabled restoration of the orbital floor, separation of the oral and nasal cavities and midface symmetry, and allowed the patient to return to normal diet as well as to restore normal speech and swallowing function. These results remained stable for the entire follow-up period of two years. This clinical case demonstrates the safety and the feasibility of composite graft engineering for the treatment of complex maxillary defects. As compared to the current gold standard of autologous tissue transfer, this patient’s benefits included decreased donor site morbidity and improved oral rehabilitation. Bone resorption of the construct at the ectopic prefabrication site still needs to be further addressed to preserve the designed graft size and shape.